2021
DOI: 10.56946/jspae.v1i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented response of wheat to irrigation levels and various rates of Nano-black carbon

Abstract: In Khyber-Pakhtunkhwa, Pakistan, wheat yield is subjected to availability of water and proper rate of Nano-black carbon in soil. Delay in rain and unsuitable soil health cause severe yield reduction. Therefore this experiment was conducted to compare Irrigation levels in relation to different rate of Nano-black carbon to find out high yielding fact that could enhance wheat productivity and food security. Three different-irrigation-levels (250-mm, 275-mm and 300-mm), were compared in early growth establishment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Additionally, the co-application of biochar and Mg fertilizer (BCM) not only increased soil pH, but also increased SOM and soil nutrients, realizing the synergistic effect of biochar and Mg fertilizer. These results indicated that interactions between biochar and Mg fertilizer affect nutrient mineralization and availability, especially N and P, as well as the uptake of basic Ex-Ca (cmol kg −1 ) 11.4 ± 0.9 c 10.9 ± 0.5 c 14.9 ± 0.6 a 12.5 ± 0.9 bc 14.0 ± 0.8 ab 12.4 ± 0. cations such as Ca 2+ , Mg 2+ and K + (Imran, 2021). Upon the addition of biochar back to the field, the aromaticity and hydrophobicity of SOM improves, leading to more stable SOM (Yang et al, 2021).…”
Section: Soil Physicochemical Propertiesmentioning
confidence: 99%
“…Additionally, the co-application of biochar and Mg fertilizer (BCM) not only increased soil pH, but also increased SOM and soil nutrients, realizing the synergistic effect of biochar and Mg fertilizer. These results indicated that interactions between biochar and Mg fertilizer affect nutrient mineralization and availability, especially N and P, as well as the uptake of basic Ex-Ca (cmol kg −1 ) 11.4 ± 0.9 c 10.9 ± 0.5 c 14.9 ± 0.6 a 12.5 ± 0.9 bc 14.0 ± 0.8 ab 12.4 ± 0. cations such as Ca 2+ , Mg 2+ and K + (Imran, 2021). Upon the addition of biochar back to the field, the aromaticity and hydrophobicity of SOM improves, leading to more stable SOM (Yang et al, 2021).…”
Section: Soil Physicochemical Propertiesmentioning
confidence: 99%